Utility of Blood Flow/Resistance Index Ratio (Qx) as a Marker of Stenosis and Future Thrombotic Events in Native Arteriovenous Fistulas - Colombo, Alessandro; Provenzano, Michele; Rivoli, Laura; Donato, Cinzia; Capria, Marinella; Leonardi, Giuseppe; Chiarella, Salvatore; Andreucci, Michele; Fuiano, Giorgio; Bolignano, Davide; Coppolino, Giuseppe (Frontiers in Surgery, 2021)
Objective:The resistance index (RI) and the blood flow volume (Qa) are the most used Doppler ultrasound (DUS) parameters to identify the presence of stenosis in artero-venous fistula (AVF). However, the reliability of these indexes is now matter of concern, particularly in predicting subsequent thrombosis. In this study, we aimed at testing the diagnostic capacity of the Qa/RI ratio (Qx) for the early identification of AVF stenosis and for thrombosis risk stratification. Methods:From a multicentre source population of 336 HD patients, we identified 119 patients presenting at least one “alarm sign” for clinical suspicious of stenosis. Patients were therefore categorized by DUS as stenotic (n=60) or not-stenotic (n=59) and prospectively followed. Qa,RI, and QX, together with various clinical and laboratory parameters, were recorded. Results:Qa and Qx were significantly higher while RI was significantly lower in non-stenotic vs. stenotic patients (p<0.001 for each comparison). At ROC analyses, Qx had the best discriminatory power in identifying the presence of stenosis as compared to Qa and RI (AUCs 0.976 vs. 0.953 and 0.804;p=0.037 and p<0.0001, respectively). During follow-up, we registered 30 thrombotic events with an incidence rate of 12.65 (95%CI 8.54-18.06) per 100 patients/year. In Cox-regression proportional hazard models, Qx showed a better capacity to predict thrombosis occurrence as compared to Qa (difference between c-indexes:0.012;95%CI 0.004-0.01). Conclusions:In chronic haemodialysis patients, Qx might represent a more reliable and valid indicator for the early identification of stenotic AVFs and for predicting the risk of following thrombosis.